In Utero Exposure to Exosomal and B-Cell Alloantigens Lessens Alloreactivity of Recipients’ Lymphocytes Rather than Confers Allograft Tolerance - Chen, Jeng-Chang; Ou, Liang-Shiou; Chan, Cheng-Chi; Kuo, Ming-Ling; Tseng, Li-Yun; Chang, Hsueh-Ling (Frontiers in Immunology, 2018)
According to actively acquired tolerance, antigen exposure before full immune development in fetal or early neonatal life will cause tolerance to this specific antigen. In this study, we aimed to examine whether allogeneic tolerance could be elicited by in utero exposure to surface MHC antigens of allogenic cells or soluble form of MHC exosomes. Gestational day 14 FVB/N fetuses were subjected to intraperitoneal injection of allogeneic major histocompatibility complex (MHC) exosomes or highly enriched B-cells. Postnatally, the recipients were examined for the immune responses to donor alloantigens by lymphocyte proliferative reactions and skin transplantation. In utero exposure to allogeneic MHC exosomes abolished the alloreactivity of recipients’ lymphocytes to the alloantigens, but could not confer skin allograft tolerance. In utero transplantation of highly enriched allogeneic B-cells generated low-level B-cell chimerism in the recipients. However, it only extended the survivals of skin allograft by a few days despite the lack of donor-specific alloreactivity of recipients’ lymphocyte. Thus, an early in utero contact with exosomal or B-cell alloantigens did not lead to full skin tolerance but rather, at best, only to delayed skin rejection in the presence of microchimerism made by B-cell inocula. These results argued against the theory of actively acquired tolerance, and implicated that in utero exposure to marrow cells in previous studies was a unique model of allo-tolerance induction that involved the establishment of significant hematopoietic chimerism. Taken together with the discovery of in utero sensitization to ovalbumin in our previous studies, the immunological consequences of fetal exposure to foreign antigens might vary according to the type or nature of antigens introduced.